Influence of screen time and sleep duration on obesity in early adolescents - Shafira Maharani Malik; Farid Agung Rahmadi; Wistiani Wistiani (Paediatrica Indonesiana, 2020)
Background Behavioral and environmental factors increase the risk of obesity. Many Indonesian children have their own smartphones and engage in excessive screen time, which may negatively impact their nutritional status and sleep duration. However, to our knowledge no studies have explained the magnitude of the influence of screen time and sleep duration on obesity in early adolescents. Objective To analyze the influence of screen time and sleep duration on obesity in children aged 10-13 years. Methods This case-control study was done from April to June 2019 in Semarang, Central Java. Subjects comprised 70 obese and 70 non-obese children, based on CDC body mass index-for-age percentiles. Subjects were recruited from 7 primary schools. Children’s screen time and sleep duration data were collected from the modified 3DPAR questionnaire. Statistical analysis was conducted using Chi-square and logistic regression tests. Results Obesity had significant associations with short sleep duration (aOR=4.20; 95%CI 1.80 to 9.78) and long computer screen time (OR=4.13; 95%CI 1.28 to 13.25). Total screen time on other media or all media combined were not associated with obesity since both the obese and non-obese groups spent >2 hours/day on screens. Short sleep duration was the dominant risk factor for obesity (OR=4.08; 95%CI 1.78 to 9.35). Conclusion Short sleep duration (<9 hours/day) is associated with and a dominant risk factor for obesity in children aged 10-13 years. However, screen time is not associated and not influential as a dominant risk factor for obesity, despite the high odds of obesity in children with long computer screen time (>2 hours/day).